2018
DOI: 10.1021/acs.macromol.7b02391
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Polyion Complex Associations

Abstract: This is an author's version published in: http://oatao.univ-toulouse.fr/25065 ABSTRACT: Polyion complex (PIC) micelles formed from the electrostatic interaction between oppositely charged polymers have been studied for their promising applications in the biomedical field as drug carriers or vectors for gene delivery. In spite of their asset of possible high drug loading, their formation process remains poorly studied. In this work, we investigate the properties of a series of PICs based on poly(ethylene oxide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Furthermore, the behavior of the high-q region of the scattering curves (I(q)  q -1.5 ) was described, with an additional contribution to the model which takes into account the inter-chain interactions among the two polymer components. [14] The scattering curve relative to R=0.5 clearly shows the presence of populations of different sizes: two well defined Guinier regions can be recognized as corresponding to nano-objects with an average Rg of 13 nm and Rg=151 nm, respectively. Additionally, at high-q, the contribution to the scattering signal due to polymer inter-chain interactions is higher with respect to the curve at R=1, suggesting the presence of free polymer chains in solution.…”
Section: Formation Of Polyion Complex Aggregates and Their Characterization At Room Temperaturementioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the behavior of the high-q region of the scattering curves (I(q)  q -1.5 ) was described, with an additional contribution to the model which takes into account the inter-chain interactions among the two polymer components. [14] The scattering curve relative to R=0.5 clearly shows the presence of populations of different sizes: two well defined Guinier regions can be recognized as corresponding to nano-objects with an average Rg of 13 nm and Rg=151 nm, respectively. Additionally, at high-q, the contribution to the scattering signal due to polymer inter-chain interactions is higher with respect to the curve at R=1, suggesting the presence of free polymer chains in solution.…”
Section: Formation Of Polyion Complex Aggregates and Their Characterization At Room Temperaturementioning
confidence: 95%
“…The measured SAXS profiles were normalized to an absolute scale using the standard procedure reported elsewhere. [14] A combination of two sample-todetector distances (10 and 1 m) was employed, covering a total q-range from 0.01 to 6 nm −1 . q is the scattering wave vector defined as q = (4π/λ) sin ϑ/2, λ being the wavelength (λ ∼ 1 Å) and ϑ the scattering angle.…”
Section: Small-angle X-ray Scattering (Saxs)mentioning
confidence: 99%
“…In the literature PICs sizes ranging from some tenths of nanometers to few hundred of nanometers have been reported [30]. We have previously demonstrated that the size and the internal structure of such self-assemblies depends on the molecular weight of the charged block in the copolymer used [31,32]. In order to confirm the presence of peptide P6 in the interior of the self-assemblies, both absorption and fluorescence measurements were performed.…”
Section: Figure 1 Morphological and Size Distribution Features Of Peo-paa Alone P6 Alone And Pics Micelles A Visualization Of The Differementioning
confidence: 99%
“…More recently, highly branched PAAs gained attention for their ability to (i) mimic globular proteins, so called ‘proteinoids’, which can be studied as mock proteins or peptides for their interaction with various environments [ 6 , 7 , 8 , 9 ] and were mentioned as early as 1958 in this capacity by Fox and Harada [ 10 ], and (ii) interact with biologically relevant molecules. The latter one has become the more intensely researched area as PAAs lend themselves to a multitude of biomedical applications, including the delivery of drugs [ 11 , 12 , 13 ] and nucleotides, for a review see Kataoka [ 14 ], and as imaging reagents, [ 15 , 16 ] and tissue adhesives [ 17 , 18 ] and most recently in the development of theranostics [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%